Influence of cardiovascular drugs on the efficacy and safety of dapagliflozin in patients with type 2 diabetes mellitus in the DECLARE-TIMI 58 trial. (14th October 2021) - Oyama, K; Raz, I; Cahn, A; Goodrich, E; Bhatt, D; Leiter, L; McGuire, D; Wilding, J; Gause-Nilsson, I; Mosenzon, O; Sabatine, M; Wiviott, S
Abstract: Background: In DECLARE-TIMI 58, the sodium glucose co-transporter 2 inhibitor (SGLT2i) dapagliflozin reduced the risk of the composite of cardiovascular (CV) death or hospitalization for heart failure (HHF) in a broad range of patients with type 2 diabetes mellitus (T2DM). SGLT2i are known to have diuretic and anti-hypertensive effects. However, whether concomitant CV drugs influence the efficacy and safety of dapagliflozin in these populations is less well known. Purpose: We examined whether dapagliflozin consistently reduced the risk of CV outcomes and whether the safety of dapagliflozin was similar with or without the concurrent use of various CV drugs. Methods: DECLARE–TIMI 58 was a randomized trial of dapagliflozin versus placebo in patients with T2DM and either atherosclerotic cardiovascular disease (ASCVD) or multiple risk factors for CV disease followed for a median of 4.2 years. We stratified patients by the use of CV drugs at baseline commonly used for heart failure: angiotensin-converting-enzyme inhibitors or angiotensin-receptor blockers (ACEi/ARB), beta-blockers, diuretics, and mineralocorticoid receptor antagonists (MRA). Efficacy outcomes of interest were the composite of CV death/HHF and HHF alone. We used the Cox proportional-hazard model for these analyses. Results: Of 17, 160 patients, 13, 950 (81%) used ACEi/ARB, 9, 030 (53%) used beta-blockers, 6, 967 (41%) used diuretics, and 762 (4%) used MRA at baseline. All were balanced by randomized treatment groups. Patients using CV drugs at baseline had a greater prevalence of atherosclerotic risk factors and established CV disease than those without. Dapagliflozin consistently reduced the risk of CV death/HHF regardless of the use of CV medications (Figure). For HHF alone, similar results were seen with no significant interactions for any of the classes. There were no significant treatment interactions by the concomitant use of any of CV drugs for adverse events including symptoms of volume depletion or acute kidney injury. Conclusions: In this analysis from the DECLARE–TIMI 58 trial, dapagliflozin consistently reduced the risk of CV death/HHF and HHF alone irrespective of the concurrent use of various CV drugs without any treatment interaction for key safety events. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The DECLARE–TIMI 58 trial was supported by AstraZeneca.